Challenges in Learning Legal English from Students’ Perspective at Hanoi Law University - Nhac, Huong (International Journal of Language and Literary Studies, 2021)
Legal English, also known as Language of the Law (Mellinkoff, 2004), is an dispensible factor contributing to the development of legal field. At Hanoi Law University, Legal English is a compulsory subject in the syllabus of legal English majors and International Trade Law majors. The question that what obstacles students face when dealing with legal English, however, has not been fully answered at this institution. This present research,which makes use of survey questionnaires as the main method, aims to study the challenges of learning legal English from the students’ perspective. The results indicate notable difficulties arising from the distinctive characteristics of legal English, differences in legal systems between jurisdictions and insufficient background knowledge of the laws. It is expected that these findings propose a number of practical recommendations in order to improve the effectiveness of the process of learning and teaching legal English.